Peer-provided Problem Management Plus (PM+) for adult Syrian refugees: a pilot randomised controlled trial on effectiveness and cost-effectiveness. (18th August 2020) - de Graaff, A. M.; Cuijpers, P.; McDaid, D.; Park, A.; Woodward, A.; Bryant, R. A.; Fuhr, D. C.; Kieft, B.; Minkenberg, E.; Sijbrandij, M.
Abstract: Aims: Common mental disorders are highly prevalent among Syrian refugees. Problem Management Plus (PM+) is a brief, transdiagnostic, non-specialist helper delivered, psychological intervention targeting psychological distress. This single-blind pilot randomised controlled trial (RCT) on PM+ delivered by peer-refugees examined trial procedures in advance of a definitive RCT, evaluated PM+ 's acceptability and feasibility, and investigated its likely effectiveness and cost-effectiveness among Syrian refugees in the Netherlands. Methods: Adult Syrian refugees ( N = 60) with elevated psychological distress (Kessler Psychological Distress Scale (K10) score >15) and reduced pychosocial functioning (WHO Disability Assessment Schedule 2.0 (WHODAS) score >16) were randomised into PM+ in addition to care as usual (CAU) (PM+/CAU; n = 30) or CAU alone ( n = 30). Primary outcomes were symptoms of depression and anxiety (Hopkins Symptom Checklist; HSCL-25) at 3-month follow-up. Secondary outcomes were pychosocial functioning (WHO Disability Assessment Schedule; WHODAS 2.0), symptoms of posttraumatic stress disorder (PTSD) (PTSD Checklist for DSM 5; PCL-5) and self-identified problems (Psychological Outcomes Profiles; PSYCHLOPS). Changes in service utilisation and time out of employment and/or adult education were estimated (adapted version of the Client Service Receipt Inventory; CSRI). Semi-structured interviews on the implementation of PM+ were conducted with stakeholders (i.e. six PM+ participants, five non-specialist helpers and five key informants). Results: Recruitment, randomization and blinding procedures were successful. PM+ was generally perceived positively by stakeholders, especially regarding the intervention strategies, accommodation of the intervention and the helpers. Two serious adverse events not attributable to the trial were reported. At 3-month follow-up, the HSCL-25 total score was significantly lower for the PM+/CAU group ( n = 30) than CAU group ( n = 30) ( p = 0.004; d = 0.58). Significant differences in favour of PM+/CAU were also found for WHODAS psychosocial functioning ( p = 0.009, d = 0.73), PCL-5 symptoms of PTSD ( p = 0.006, d = 0.66) and PSYCHLOPS self-identified problems ( p = 0.005, d = 0.81). There were no significant differences in mean health service costs ( p = 0.191) and the mean costs of lost productive time ( p = 0.141). This suggests PM+ may potentially be cost-effective with an incremental cost from a health system perspective of €5047 (95% CI €0–€19 773) per additional recovery achieved. Conclusions: Trial procedures and PM+ delivered by non-specialist peer-refugee helpers seemed acceptable, feasible and safe. Analyses indicate that PM+ may be effective in improving mental health outcomes and psychosocial functioning, and potentially cost-effective. These results support the development of a definitive RCT with a larger sample of refugees and a longer follow-up period.